Simple Linear Regression Method to Predict Cooking Oil Prices in the Time of Covid-19 - Lilis Harianti Hasibuan; Darvi Mailisa Putri; Miftahul Jannah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
The background of this research is the soaring price of cooking oil during the Covid-19 period which continues to increase in the city of Padang. The research method used is a case study of data on cooking oil prices in the city of Padang. The purpose of this study is to obtain predictions of cooking oil prices. Linear regression is used as a prediction method for cooking oil prices in the next X(t) period. The research method used is a case study using simple linear regression. In this study, the actual cooking oil price Y(t) is the effect variable and the time period is the causal variable. The linear regression equation obtained is Y'=25239+124.56X. Testing the accuracy of the prediction results using RMSE with a value of 0.1913. The prediction of cooking oil prices using the linear regression method can be said to be in the very good category, it can be seen that the RMSE value is very small in the test and meets the standards.